APLIKASI SEMIOTIKA NARATIF A. J. GREIMAS TERHADAP KISAH THALUT DALAM AL-QUR’AN - Makdis, Nasrul; dri, Jen; valina, Del; ismail, Lusi (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2024)
This research aims to explore the case of the Thalut story in the Koran by borrowing the narrative semiotic theory of A.J. Greimas. This structural theory is expected to be able to explore the text structure of the Al-Qur'an. Apart from that, narrative semiotic theory also opens up a new understanding of the text by looking at the outer structure and deeper inner structure of the text. An understanding that is not new, but is able to carry a slightly different meaning than most. In this paper, it is found that with narrative semiotic theory, the meaning of the Koran becomes broader and is not only focused on textual understanding